Kualitas Dange Yang Disubstitusi Tepung Daging Ikan Kembung (Rastrellinger kanagurta) - Ambar Rukmini; Kuntjahjawati Kuntjahjawati; Supriasri Supriasri (Universitas Muhammadiyah Yogyakarta, 2014)
Dange is a traditional food made from delicate wet sago starch and further roasted in forna. Dange has rectangle form, flat with approximately 0,5 cm thickness. In addition, dange is also well known for its light, tasteless, hardness and relatively not hygroscopy. To increase the quality of dange and improve its flavour, a research was performed to study the quality of dange substituted with mackerel fish meat. The treatment was arranged in two classifications factorial completely randomized design. The classifications were variation of mackerel fish meat (0%, 2%, 5% and 8%) and time of grill (1 minute, 2 minutes and 3 minutes). Furthermore, the dange product quality was tested chemical and sensory analysis. The chemical analysis consisted of moisture, protein, fat, ash and starch content. Whereas the different of dange product quality was tested sensory analysis using scoring test method and the consumers acceptance was tested by hedonic scale test method. It was found that the most liked dange was made from 5% substitute of mackerel fish meat at 1 minute grill. This dange had slightly brittle texture, yellow-white colour, fishy taste and relatively strong fishy flavour with 27.84% moisture, 3.98% protein, 0.50%fat, 2.48% ash and 57,78% starch content.